Unraveling the link: environmental tobacco smoke exposure and its impact on infertility among American women (18–50 years) - Peng, Liang; Luo, Xiaohan; Cao, Baodi; Wang, Xiaohui (Frontiers in Public Health, 2024)
Purpose The detrimental effects of environmental tobacco smoke (ETS) on women’s reproductive health have been widely recognized. However, the detailed association between exposure to environmental tobacco smoke and the incidence of infertility remains under-explored. This investigation focuses on exploring this potential connection. Methods For this analysis, we extracted data from the US National Health and Nutrition Examination Survey (NHANES) database, covering the years 2013 to 2018, focusing on individuals with recorded serum cotinine levels and infertility information. ETS exposure and fertility status were analyzed as independent and dependent variables, respectively. We applied weighted multivariate logistic regression method to evaluate the impact of ETS on infertility, including subgroup analyses for more detailed insights. Results The study encompassed 3,343 participants. Logistic regression analysis revealed a notable positive correlation between ETS exposure and infertility, with an odds ratio (OR) of 1.64 (95% Confidence Interval [CI]: 1.14–2.36). We observed a non-linear relationship between ETS exposure and infertility risk. Notably, infertility risk increased by 64% in serum cotinine levels above 0.136 compared to that in serum cotinine levels below 0.011. Further, subgroup analysis and interaction tests showed consistent results across different segments, underscoring the robustness of the ETS-infertility link. Conclusion Our findings suggest that environmental tobacco smoke exposure may be a contributing factor to infertility. These results reinforce the recommendation for women in their reproductive years to avoid ETS exposure, especially when planning for pregnancy.